Precision of age estimates from different ageing structures of Labeo bata (Hamilton) collected from river Ganga, India - Khan, Shahista; Afzal Khan, M.; Miyan, Kaish (Indian Journal of Fisheries, 2015)
Scales, opercular bones, vertebrae and otoliths collected from Labeo bata, inhabiting river Ganga were used to identify the most suitable structure for age estimation. Age estimates were evaluated between readers and between pairs of ageing structures by calculating the percent agreement, average percentage of error and coefficient of variation. Percent agreement between readers was highest for scales (87%), followed by opercular bones (81.2%), vertebrae (78.9%) and otoliths (76%). Due to highest values of percent agreement, lowest average percent error and coefficient of variation values between two readers, scales were considered to be the most suitable structure for age estimation of L. bata. When age of scales were compared with other alternative structures viz., opercular bones, vertebrae and otoliths, the highest percent agreement (72.7%), lowest average percent error (7.61%) and coefficient of variation (10.77%) values were found between scales and opercular bones. Also, mean values of age estimates from scales were comparable (p>0.05) to those obtained from opercular bones, and were significantly (p